Simulations in undergraduate nursing programmes in New Zealand: current status and next steps. (20th July 2016) - Lesa, Raewyn; Daniel, Ben
Abstract : Introduction: There is an increasing global tendency to use simulations in nursing education. This research examined the current status of simulation programs in undergraduate nursing schools in New Zealand. The goal was to gain a better understanding of how simulations are currently implemented in nursing schools and to identify the associated opportunities and challenges. Methods: 16 nursing schools in New Zealand deliver undergraduate nursing education. 10 of these schools selected a nursing leader who was involved in the schools' simulation program to complete an online survey. The survey questions were designed to explore the nature of simulations in nursing schools, and the opportunities and challenges experienced in the implementation of these programmes. Data analysis: Survey data were analysed and presented as summary statistics (frequencies and percentages). Responses to short questions were thematically analysed and common themes were identified. The analysis was divided into demographic characterises and main results. Results: The key outcomes of the study have shown the prevalence of various simulation modalities in nursing schools in New Zealand. The analysis also suggests that the current practices associated with the integration of simulations into nursing education in New Zealand are fragmented and sporadic. Challenges shared across all institutions include inadequate resourcing of simulation programs, poor curriculum integration and programme alignment; a lack of shared understanding of what constitutes simulation and the extent to which simulation modalities achieve learning outcomes. Conclusions: The outcome of this study has contributed to a better understanding of the prevalence and nature of simulation programs in undergraduate nursing schools in New Zealand. It has also provided insights into the different opportunities and challenges associated with implementing these programmes in nursing schools. Furthermore, the research has identified important conceptual and theoretical issues related to the broad discourse on the use of simulations in undergraduate nursing education.